The cash-flow channel of monetary policy: Evidence from billions of transactions - SeHyoun Ahn; Sigurd Mølster Galaasen; Mathis Mæhlum (Norges Bank, 2024)
We present novel findings on the impact of monetary policy on consumer spending behavior using a newly assembled high-frequency household expenditure panel. Leveraging comprehensive weekly electronic transaction-level data for all individuals in Norway over 13 years, our study sheds light on the high-frequency consumption response to monetary policy through changes in fast-moving net interest expenses. We employ several identification strategies, including household-specific interest rate shocks arising from a natural experiment and high-frequency monetary policy instruments. We find a substantial shortrun consumption response to changes in interest payments. Relative to households with no interest exposure, households at the 90th percentile cut consumption by 1 - 1.5 percent of income within a year of a 1 percentage point policy rate hike. Our results imply a substantial marginal propensity to consume out of net interest payments, and they indicate the presence of a strong cash-flow channel of monetary policy.
hdl:11250/3177167
Keywords: D12; D31; E21; E43; E52; G51; 330; Monetary policy transmission; Household Consumption; Debt; Interest rates; Marginal propensity to consume; High frequency